Intrahepatic portal occlusion by microspheres: a new model of portal hypertension in the rat. Issue 6 (June 1994) - Jaffe, V; Alexander, B; Mathie, R T
Abstract : Available experimental models of portal hypertension are based either on cirrhosis or externally applied portal vein constricting devices. A new method is described of raising portal pressure, which uses intraportally injected microspheres to block intrahepatic portal radicles, which has the advantages of retaining normal liver architecture and providing a more clinically relevant intrahepatic obstruction to portal flow. Measured aliquots of microspheres (15, 25, 50, 90 microns) or equivalent volumes of saline were injected into a peripheral portal tributary (caecal vein) of 22 normal rats. The resultant changes in arterial, portal, and splenic pulp pressures were monitored. Sequential microsphere injections produced graduated rises in portal pressure up to a peak of 18.5-22.5 mm Hg (8.7-12.4 mm Hg increase from basal), which declined gradually to a steady state pressure of 13.3-15.1 mm Hg (4.0-5.0 mm Hg increase). There was no significant difference between pressure increases produced by microspheres of differing sizes. It is concluded that portal hypertension can be produced acutely by blocking portal radicles with microspheres. The maximum pressure achieved, however, is substantially less than that obtained by total portal vein occlusion (mean: 57.6 mm Hg). This suggests the existence of functional intrahepatic portal systemic shunts not previously described in the normal liver.